The Effect of Advocacy on Understanding and Levels of Blood Glucose in Diabetes Mellitus Patients - Effendi, Mustofa Helmi (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Diabetes mellitus (DM) is a serious health problem worldwide. The unhealthy lifestyles, such as smoking, lack of physical activity, high glucose/calories intake, and alcohol consumption, are thought to be the risk factors for diabetes. Uncontrolled blood glucose level will increase the risk of complications such as microvascular and neuropathy. Patient’s knowledge of DM and medication administration is required to prevent the complication of diabetes. Patient advocacy can increase the patient’s knowledge. Materials and Methods: The purpose of this study was to determine the influence of patient advocacy on their knowledge of medication administration and decrease in blood glucose levels. This pre-experimental one-group pretest-posttest study was conducted on 58 patients with DM. The collected data were including blood glucose level and patient’s knowledge. A questionnaire was used to collect the data of patient’s knowledge. Data were analyzed using paired t-test. Results: The results showed the average knowledge before advocacy was 7.07, while the average blood glucose level was 239.48 mg/dL. After patient advocacy program, average knowledge was 7.95, while the blood glucose level was 208.52 mg/dL. Discussion and Conclusion: It can be concluded that patient advocacy increases patient’s knowledge of drug administration and influences the decrease in blood glucose levels.